Civil engineering PE practice exams breadth and depth - Goswami, Indranil (McGraw-Hill, 2012)
This book contains 280 questions divided into seven 40-question clusters. There are two breadth exams representative of the NCEES guidelines for the principles and practice of civil engineering. These exams are followed by five depth exams: structural depth; geotechnical depth; water resources and environmental depth; transportation depth; and construction depth. Detailed solutions for all of these exams are provided.